MEN AND SPORT SOCIALIZATION TO MASCULINITY - Modzelewska, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Socialization as a long-life process is an extremely important element of every human's life. From a early years every child is taught the right behaviour in the social space. One of the areas in which we are socialized are the behaviours and the roles of each gender. Little girls are taught behaviours based on empathy and care while boys are guided towards diverse physical activities. Sport then becomes a space where boy learns behaviours that are considered by the society to be proper for the men. Features described as "typically male" which boys learn while doing sports include domination, aggression or competition. Learned desire to dominate in this space is one of the determinants of Pierre Bourdieu's habitus of men. Domination structures are also the product of endless reproduction processes which results in the duplication of behaviour patterns including in the case of gender roles. Men and women are the main victims and prisoners of contemporary dominant cultural ideas. Not only the fact of doing sports is perceived as an appropriate socialization for masculinity but also being a fan  is an area of "proper gender socialization".  Sport as a space of manifestation by men of their strength and courage is also an exemplification of the hegemonic masculinity presented by Raewyn Connell.